The Community’s Role in Realising Sustainable Tourism in Ubud District, Bali - Nurrohmah, Novita Dewi; Sitohang, Lidya Lestari; Rachmawati, Hilma; Rahayu, Reny Hari Puji; Ichsan, Moch Syaiful (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
Ubud has become a popular destination for sustainable tourism, resulting in an increase in visitors to the region. Local communities have responded to tourist demand by providing accommodation, food and other visitor services. The community's income-generating activities now include tourism as a crucial component. However, the success of promoting sustainable tourism has led to overtourism in the region. This study aims to analyse how the community can maintain sustainable tourism and at the same time ensure the sustainability of their income generating activities. Data collection including observation, documentation, interviews, and literature review. Purposive sampling was used as the sampling technique, and triangulation techniques were employed in the analysis to ensure data validity. This paper presents empirical evidence of the local community role in achieving sustainable tourism. The results show that the local community’s roles can be categorised as either spontaneous or induced participations.